"Robots Vs Animals": Establishing a Culture of Public Engagement and Female Role Modeling in Engineering Higher Education. (April 2017) - Fogg-Rogers, Laura; Sardo, Margarida; Boushel, Corra
A widespread culture supporting public engagement activities in higher education is desirable but difficult to establish. Drawing on social cognitive theory, this science communication project aimed to enhance culture change in engineering by developing communication skillsets of early-career engineers, particularly supporting female engineers as role models. Engineers received training in storytelling to present at live events, enhanced by peer group social persuasion and vicarious modeling. A science communication coordinator and senior management endorsement removed barriers to participation. Evaluation showed engineers' self-efficacy levels significantly increased. Qualitative data highlighted a developing culture of engagement but purposive selection of women proved controversial.